Optical Properties of Luminescent Materials - Ribeiro, Sidney J.L. [UNESP]; dos Santos, Molíria V. [UNESP]; Silva, Robson R. [UNESP]; Pecoraro, Édison [UNESP]; Gonçalves, Rogéria R.; Caiut, JoséMaurício A. (Wiley, 2015)
Summary: Sol-gel methods (SGMs) are nowadays well established and developed giving birth to a wonderful collection of new multifunctional materials only possible to be obtained due to the intrinsic flexibility and low temperatures involved. This chapter concerns luminescence or in the general sense the emission of light under appropriate excitation, dealing mainly with luminescence properties brought by active species added to a given host, i.e., lanthanide ions (Ln) and dyes. It mentions some of the important work being done in the last years concerning materials obtained by the SGM. Frequency conversion is one of the attractive properties displayed by Ln-doped materials mainly due to the richness of the energy-level structure and long-lived states. Ln-based upconverters are important alternatives to conventional downshifting luminescent markers in many different applications, for example, biological systems. The organic dye rhodamine 6G was one of the first luminescent species studied, encapsulated in silica obtained by the SGM.
Keywords: Downconversion; Luminescent materials; Near-infrared emitters; Optical properties; Organic dyes; Sol-gel method; Visible emitters downshifting